FORMULATION AND CHARACTERIZATION OF SELF NANO-EMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) FRACTION OF N-HEXANE: ETHYL ACETATE FROM SESEWANUA LEAF (CLERODENDRUM FRAGRANS WILD.) - SAPIUN, ZULFIAYU; IMRAN, ARLAN K.; ROSMALA DEWI, SISILIA TERESIA; MASITA PADE, DHEA FADILA; IBRAHIM, WIDYAWATI; TUNGADI, ROBERT; ABDULKADIR, WIDY SUSANTI; BANNE, YOS; RIFAI, YUSNITA; SARTINI, SARTINI; et al. (International Journal of Applied Pharmaceutics, 2023)
Objective: Sesewanua leaves contain alkaloid compounds as antioxidants, and its leaves can be used to formulate SNEDDS dosage forms, which can effectively deliver the medicine. This study intended to determine the variation of surfactant concentration (Tween 80) and cosurfactant (PEG 400) towards pH, viscosity, nano-emulsion duration and characterization using PSA method (particle size and polydispersity index). Methods: This study employed a quasi-experimental method and the independent variables in this study were variations in the concentration of surfactant (Tween 80) and cosurfactant (PEG 400), which consist of 3 formulas, such as SFS 1 (6:3), SFS 2 (7:2), and SFS 3 (8:1). The dependent variables in this study including pH, viscosity, nano-emulsion time, particle size and polydispersity index which utilized One Way Anova Post Hoc LSD (p>0.05) and Tamhane (p<0.05) tests as the data analysis. Results: The pH test SFS1-SFS3 has a pH value of 7.92, 8.30 and 8.35, followed by Viscosity test SFS1-SFS3, which has a viscosity value of 1.00 cP, 1.38 cP and 2.91 cP. Further, the SFS1-SFS3 nano emulsified time test had nano emulsified time in gastric and intestinal fluids 35.18s and 43.96s, 43.54s and 47.13s and 44.00s and 50.29s. Characterization of SFS1-SFS3 particle size in gastric and intestinal fluids 23.9 nm and 23.0 nm, 18.5 nm and 22.7 nm and 19.1 nm and 22.9 nm, while characterization of SFS1-SFS3 polydispersity index in gastric and intestinal fluids were 0.433 and 0.348, 0.451 and 0.440 and 0.568 and 0.462. Conclusion: The increase of variations in surfactant concentration and decreased cosurfactant significantly affected pH, viscosity, nano-emulsion time, and particle size of SFS preparations. However, the polydispersity index was not considerably affected.